2023
DOI: 10.3390/ani13030496
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Parasites of Dogs in Egypt: An Update on the Prevalence in Dakahlia Governorate and a Meta-Analysis for the Published Data from the Country

Abstract: Since the last survey on gastrointestinal (GIT) parasites infecting dogs in Dakahlia governorate, Egypt, was published 40 years ago, the present study detected various GIT parasites in feces of 78 stray dogs in this governorate. Twenty-one dogs (35.9%) had eggs/oocysts of eight different parasites including Toxocara canis (19.2%), Toxascaris leonina (2.6%), hookworms (1.3%), Taenia species (5.1%), Dipylidium caninum (2.6%), Cystoisospora canis (5.1%), Cystoisospora ohioensis (2.6%), and Neospora caninum-like o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The presence of T. gondii -like oocysts in the feces of cats in Egypt may have been overestimated, where 1432 cats were examined, revealing a pooled prevalence of 11.9% [ 64 ]. Neospora caninum -like oocysts were found in the feces of one of 78 dogs tested in a single study (Dakahlia governorate), and it is conceivable that certain small-sized oocysts detected in prior studies from Egypt are N. caninum [ 65 ]. Furthermore, N. caninum -like oocysts were found in the feces of five of nine puppies fed the placentas and brains of nine aborted bovine fetuses in Egypt [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of T. gondii -like oocysts in the feces of cats in Egypt may have been overestimated, where 1432 cats were examined, revealing a pooled prevalence of 11.9% [ 64 ]. Neospora caninum -like oocysts were found in the feces of one of 78 dogs tested in a single study (Dakahlia governorate), and it is conceivable that certain small-sized oocysts detected in prior studies from Egypt are N. caninum [ 65 ]. Furthermore, N. caninum -like oocysts were found in the feces of five of nine puppies fed the placentas and brains of nine aborted bovine fetuses in Egypt [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the estimate prevalence of dog sarcocystosis varies from 2.2 to 9% according to the worldwide reports [ 22 24 ]. Also, Abbas et al, [ 25 ] found that Sarcocystis oocysts were detected in 29 fecal samples from 1126 dogs with a very low pooled prevalence (2.0%) in Egypt, while El Menyawe and Abdel Rahman [ 26 ], and Sabry and Lotfy [ 27 ], depicted that the overall prevalence of dog sarcocystosis in Cairo and Giza governorates was 1.8% and 14.8%, respectively. In a recent study, a very low prevalence (0.3%) was recorded in dogs from Calgary, Canada [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcocystis , first reported in 1843, is a genus of intracellular protozoan parasite which belongs to Sarcocystidae family, Eucoccidiorina order of Apicomplexa phylum. Worldwide, considerable production losses and health illness in animals have been recognized due to the presence of >200 species in the genus of Sarcocystis that infects a wide array of domestic and wild animals ( Dubey et al ., 2015a ; Abbas et al ., 2023 ). The life cycle of a parasite involves two hosts; definitive (predator) and intermediate (prey) hosts.…”
Section: Introductionmentioning
confidence: 99%